Transparansi Pemerintah Dalam Realisasi Anggran Belanja Barang dan Jasa - Suwakul, Rian; Nendissa, Renny Heronia; Pattinasarany, Yohanes (Faculty of Law Universitas Pattimura, 2025)
Transparency in governance is one of the main principles in realizing good governance. Through transparency, the public is able to understand and monitor the budget management process so that it is carried out openly, efficiently, and accountably. In this regard, the Ambon City Government bears a significant responsibility to implement this principle, particularly in the realization of the goods and services expenditure budget. This study aims to examine the forms of transparency implemented by the Ambon City Government in carrying out the goods and services budget, as well as the legal consequences that may arise when the principle of transparency is not upheld. The research employs a normative juridical method with statutory and conceptual approaches. Data were obtained from laws and regulations, legal literature, and other supporting documents. The results of the study indicate that transparency within the Ambon City Government is manifested through the implementation of electronic systems such as SIRUP (General Procurement Planning Information System), LPSE (Electronic Procurement Service), and the E-Catalogue, which serve as forms of public information disclosure in accordance with Law Number 14 of 2008 on Public Information Disclosure. Through these systems, the public can access information related to the planning, implementation, and reporting of goods and services procurement in an open manner. However, in practice, several obstacles remain, including low accountability and indications of budget misuse as found by the Audit Board of Indonesia (BPK) for the years 2021–2023. A lack of transparency may result in administrative, civil, and criminal legal consequences, such as contract cancellation, sanctions against authorized officials, and liability for state financial losses. Therefore, the implementation of transparency principles is a crucial factor in realizing a clean, accountable, and publicly trusted government.